Pengaruh Persepsi Kemudahan Dan Persepsi Kemanfaatan Terhadap Pemanfaatan E-Learning Dengan Model Tam Di Smk Muhammadiyah 3 Yogyakarta - Subakdo Eko Yulianto (Universitas Muhammadiyah Yogyakarta, 2011)
This study is entitled: Influence Perceived Ease of Use and Perceived Usefulness to Use E-Learning with TAM Model in SMK Muhammadiyah 3 Yogyakarta. This research was aimed at indetifying the behavior of the e-learning with Technology Acceptance Model (TAM) approach toward the students of the SMK Muhammadiyah 3 Yogyakarta. The proposed hypothesis in this research were (a) Perceived Ease of Use has a positive and significant effect to the use of e-learning, (b) Perceived Usefulness has a positive and significant effect to the use of e-learning. The samples in this research were 50 respondents in SMK Muhammadiyah 3 Yogyakarta. The data gained through the primary data by distributing a questionnaire to be answered. The data analysis was conducted by using SPSS program. The result of the research showed that (a) Perceived Ease of Use has a positive and significant effect to the use of e-learning and (b) Perceived Usefulness has a positive and significant effect to the use of e-learning.